HEMOLYTIC DISEASE OF THE NEWBORN - Vivi Keumala Mutiawati (Universitas Syiah Kuala, 2018)
Abstrak. Pemahaman penyakit hemolitik pada bayi baru lahir telah berubah selama beberapa dekade terakhir. Penyakit hemolitik akibat inkompatibilitas ABO dan aloantibodi lainnya kini muncul sebagai penyebab utama. Banyak negara telah mengidentifikasi aloantibodi selain anti D sebagai penyebab penyakit hemolitik dengan gejala klinis sedang sampai dengan berat. Prevalensi dan frekuensi populasi antibodi anti-A dan anti B dari golongan darah ABO berguna dalam memprediksi perkiraan anak yang lahir oleh wanita golongan darah O yang menikahi suami golongan darah bukan O yang berisiko menjadi ABO HDN. Kelainan ABO HDN disebabkan oleh antibodi IgG pada ibu disebabkan kemampuan IgG untuk melewati sawar darah plasenta. Eritrosit yang peka oleh antibodi dihancurkan oleh makrofag pada limpa janin dengan gejala klinis hiperbilirubinemia. Kelainan ABO HDN memberikan gambaran klinis yang lebih ringan pada populasi, dan ditandai dengan derajat hemolisis yang ringan. Diagnosis biasanya dilakukan dengan pemeriksaan bayi baru lahir yang telah mengalami ikterus pada hari pertama kehidupan. Keywords: Penyakit hemolitik bayi baru lahir, aloantibodi golongan darah, ikterus Abstract. The spectrum of hemolytic disease of the newborn has changed over the last decades. Hemolytic disease due to ABO incompatibility and other alloantibodies has now emerged as major causes. Many countries have identified alloantibodies other than anti D as a cause of moderate-severe hemolytic disease. The prevalence of immune anti A and anti B antibodies and the population and gene frequencies of the various ABO blood groups are useful in predicting an estimate of children born by blood group O women married to non-group O husband who are at risk of developing ABO HDN. ABO HDN is caused by IgG maternal antibodies which have the ability to cross the placental barrier. The red cells which are sensitized by the antibodies are destroyed by macrophages in fetal spleen with consequent hyperbilirubinemai. ABO HDN is described as a condition having a very low incidence in the population and characterized by a a mild degree of hemolysis. Diagnosis is usually made by investigation of a newborn baby who has developed jaundice during the first day of life. Keywords: Hemolytic disease of the newborn, blood groups alloantibodies, joundice